Colors and patterns of black hole X-ray binary GX 339-4 - Ilia A. Kosenkov; Alexandra Veledina; Valery F. Suleimanov; Juri Poutanen (EDP SCIENCES S A, 2022)
Black hole X-ray binaries show signs of nonthermal emission in the optical to near-infrared range. We analyzed optical to near-infrared SMARTS data on GX 339-4 over the 2002-2011 period. Using soft state data, we estimated the interstellar extinction toward the source and characteristic color temperatures of the accretion disk. We show that various spectral states of regular outbursts occupy similar regions on color-magnitude diagrams, and that transitions between the states proceed along the same tracks despite substantial differences in the morphology of the observed light curves. We determine the typical duration of hard-to-soft and soft-to-hard state transitions and the hard state at the decaying stage of the outburst to be one, two, and four weeks, respectively. We find that the failed outbursts cannot be easily distinguished from the regular outbursts at their early stages, but if the source reaches 16 mag in V band, it transits to the soft state. By subtracting the contribution of the accretion disk, we obtain spectra of the nonthermal component, which have constant, nearly flat shapes during the transitions between the hard and soft states. In contrast to the slowly evolving nonthermal component seen at optical and near-infrared wavelengths, the mid-infrared spectrum is strongly variable on short timescales and sometimes shows a prominent excess with a cutoff below 10(14) Hz. We show that the radio to optical spectrum can be modeled using three components corresponding to the jet, hot flow, and irradiated accretion disk.